Phosphatidylinositides regulate the cell plate morphology transition during cytokinesis in Arabidopsis - Yu Luo; Yu-Fang Tian; Hui-Ru Liu; Wei-Cai Yang (Nature Communications)
Abstract In plants, the developing cell plate which is characterized by a series of anionic lipids, undergoes dramatic morphological change for successful cytokinesis. However, the mechanisms underlying these alterations, and the roles of anionic lipids such as phosphatidylinositol-4-phosphate (PI4P), phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2), and phosphatidylserine (PS) during cell division remain poorly understood. Here we present that changes in anionic lipid composition have a profound effect on cell plate development: deprivation of phosphatidylinositides (PIPs) leads to incomplete cytokinesis through distorted cell-plate architecture. Our data demonstrate that PI4P shapes cell plate membrane morphology through flippase-regulated PS flipping inhibition, while PI(4,5)P2 functions in the recruitment of dynamin-related protein 1A (DRP1A) and the constriction region formation; depletion of PIPs causes cell plate tubulation and flattening failure. We propose a model in which PI4P regulates the level and distribution of PS, while PI(4,5)P2 mediates the localization of DRP1A; together, they coordinate cell plate morphology to ensure successful cytokinesis in plant cells.